Control of a SMES for mitigating subsynchronous oscillations in power systems: A PBC-PI approach (2018)
This paper proposes a methodology to control the active and reactive power of a superconducting magnetic energy storage (SMES) system to alleviate subsynchronous oscillations (SSO) in power systems with series compensated transmission lines. Primary frequency and voltage control are employed to calculate the active and reactive power reference values for the SMES system, and these gains are calculated with a particle swarm optimization (PSO) algorithm. The proposed methodology is assessed with a classical PI controller, feedback linearization (FL) controller and a passivity-based PI control (PI-PBC). Operating limits for VSC are also considered, which gives priority to active power over reactive power. The IEEE Second Benchmark model is employed to demonstrate the assessment of the proposed methodology where PI-PBC presents better performance than the classical PI and FL controllers in all the operating conditions considered. © 2018 Elsevier Ltd